Lao People's Democratic Republic : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1996)
This paper reviews economic developments in Lao People's Democratic Republic (PDR) during 1992-95. To highlight in more detail the factors that contributed to Lao PDRs macroeconomic performance during 1992-95, the paper analyzes the developments in macroeconomic variables and policy actions. It also notes that real GDP growth, averaging about 7 percent during 1992-95, was attributable to a rapid expansion of manufacturing, construction, and tourism, as well as strong growth in agriculture in 1992 and 1994.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet